COLLABORATION BETWEEN CHILDREN, FAMILY AND TEACHERS, IN PROMOTING CHILD’S LEARNING SKILLS - Vanaga, Asja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Partnership between teacher and parents forms understanding about mutual communication and the benefits for learning process out of that. Teacher’s observations points to a different understanding on the collaboration with children as a successive process in setting and achieving learning goals. The aim of the article is to reveal how to turn the initiative to involve in preschool learning process expressed by family, into planned engagement in learning process. Daily activities planned by teacher turns parents into educators and involves whole family into initiative fostering project, which strengthens overall partnership between teacher, child and family.